Healthcare-associated fungal infections and emerging pathogens during the COVID-19 pandemic - Shah, Krish; Deshpande, Mukund; Shah, P. (Frontiers in Fungal Biology, 2024)
Historically, fungi were mainly identified as plant and insect pathogens since they grow at 28°C. At the same time, bacteria are known to be the most common human pathogens as they are compatible with the host body temperature of 37°C. Because of immunocompromised hosts, cancer therapy, and malnutrition, fungi are rapidly gaining attention as human pathogens. Over 150 million people have severe fungal infections, which lead to approximately more than one million deaths per year. Moreover, diseases like cancer involving long-term therapy and prophylactic use of antifungal drugs in high-risk patients have increased the emergence of drug-resistant fungi, including highly virulent strains such as Candida auris. This clinical spectrum of fungal diseases ranges from superficial mucocutaneous lesions to more severe and life-threatening infections. This review article summarizes the effect of hospital environments, especially during the COVID-19 pandemic, on fungal infections and emerging pathogens. The review also provides insights into the various antifungal drugs and their existing challenges, thereby driving the need to search for novel antifungal agents.